Is There A Safe Limit of Delay for Emergency Caesarean Section in Ghana?: Results of Analysis of Early Perinatal Outcome - Oppong, S.A.; Tuuli, M.G.; Seffah, J.D.; Adanu, R.M.K. (Ghana Medical Journal, 2014)
Objective: To determine the limits of delaying caesarean section in a busy obstetric unit in a developing country setting that is not associated with neonatal survival. Methods: Retrospective cohort study of emergency cesarean sections. Indications were sub-divided into imminent threat and no imminent threat to fetal wellbeing. The primary outcomes was a composite measure of adverse perinatal outcome including stillbirth, 5- minute Apgar score < 7 and neonatal intensive care unit admission. Effect of decision-to-delivery interval on perinatal outcomes was evaluated using Kaplan- Meier survival analysis. Results: 495 women met inclusion criteria (142 ‘imminent threat’ group, 353 ‘no imminent threat’ group). The median decision-to-delivery interval was significantly shorter in the ‘imminent threat’ group (2.25 [95% CI 1.38 - 5.83] versus 3.42 [95% CI 1.83 - 5.85] hours, p <0.001). Only 1.7% and 12.7% sections were performed within 30 minutes and 1 hour, respectively. Risk of the composite outcome was significantly higher in the ‘imminent threat group (46.5% versus 31.2%, RR=1.49 [95% CI 1.18 – 1.89], p=0.001). A 95% probability of ‘live intact’ survival occurred at 1hr and 2hrs respectively, for the imminent threat and the no imminent threat groups Conclusion: Increasing decision-to-delivery interval is associated with higher risk of adverse perinatal outcomes, but a 95% live intact survival can be achieved if the delivery occurs within 2 hours.
Journal Article on Emergency Caesarean Section
Keywords: Limits of delay; caesarean section; Ghana; perinatal outcome